Review of Hannah ČULÍK-BAIRD, Cicero and the Early Latin Poets - Magnavacca, Adalberto (Ciceroniana On Line, 2023)
Review of Hannah ČULÍK-BAIRD, Cicero and the Early Latin Poets, Cambridge University Press, Cambridge 2022, XIV + 306 pp., ISBN 9781316516089 (hardback); 9781009031820 (ebook).